Agribusiness entrepreneurship development strategy in East Java for welcoming ASEAN Economic Community (AEC) era - Dewie Tri Wijayati (Journal of Economics, Business, and Accountancy Ventura, 2016)
Facing the implementation of ASEAN Economic Community (AEC) at the end of 2015 requires strategic measures to make Indonesia ready to compete with other nations in ASEAN. East Java Province has great potentials and contributions in the national agribusiness. Establishing agribusiness in East Java towards increased competitiveness is the right step to welcome AEC 2015. This research attempts to study the appropriate model of agribusiness development strategy for East Java. The selection of strategy model is expected to prepare a strong and competitive economy in East Java. Through three principles of data analysis model of Miles and Huberman with the emphasis on data collection, data display, and verification, this study also used a variety of data collection techniques and verifications such as Focus Group Discussion (FGD), observation, and others. This research was conducted in four regions as the focus of the study area: Probolinggo District, Sidoarjo District, Pasuruan District and the City of Batu. The results provide the following conclusions: (a) the agribusiness development strategy in East Java should be done with the target approach. This means that the introduction to the target is the most important factors to determine the strategy to be implemented; (b) the role of the government is highly important and strategic in developing agribusiness in East Java. These can be implemented through a variety of program models that are tailored to the target.